Prediction of stroke risk in patients with transient ischemic attack: ABCD score and its derived scores - Xin-Tong, Wu; Jin-Bo, Chen; Wen-Xiang, Xu; Wen-Xian, Lu (International Journal of Research in Medical Sciences, 2017)
Transient Ischemic Attack (TIA) is a high-risk signal of acute ischemic cerebrovascular disease, indicates a significant increase in the risk of ischemic stroke, especially within 7 days. Risk assessment and stratification are important in patient with TIA. A variety of simple prediction scales were developed based on the risk factors for stroke in patients with TIA, such as the California scale, ABCD scale, and ABCD2 scale. Among them, the ABCD scale score is used most commonly, but as its application becomes more and more common, the defects of this scale are also increasingly apparent. In recent years, some derived scales of ABCD score were introduced in order to improve the sensitivity and specificity of prediction. This article reviews the evolution, contents, characteristics, and predictive value of the ABCD score and its derived scales in the prediction of the stroke risk in patients with TIA.